2016
DOI: 10.1080/17461391.2015.1135984
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional kinematics of competitive and recreational cyclists across different workloads during cycling

Abstract: Although the link between sagittal plane motion and exercise intensity has been highlighted, no study assessed if different workloads lead to changes in three-dimensional cycling kinematics. This study compared three-dimensional joint and segment kinematics between competitive and recreational road cyclists across different workloads. Twenty-four road male cyclists (12 competitive and 12 recreational) underwent an incremental workload test to determine aerobic peak power output. In a following session, cyclist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 43 publications
3
24
1
Order By: Relevance
“…At finish effectiveness of cyclists resulting forces increases [27]. Our results concord well with other data and are confirmed by them [2,3,6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At finish effectiveness of cyclists resulting forces increases [27]. Our results concord well with other data and are confirmed by them [2,3,6].…”
Section: Discussionsupporting
confidence: 91%
“…The authors found that distribution of joint torques and powers is mainly sustained in different conditions of pedaling [2]; For assessment of joint and segment movements working load of from 65 to 95% from maximal output power of separate cyclists can be used [3]; Dependences of power pedal's output and electromyography (EMG) of lower limb in different cyclic position. Besides, in this work the authors determined indicators of bilateral asymmetry of pedaling force and EMG.…”
Section: Introductionmentioning
confidence: 99%
“…For example, competitive handcyclists had a 2.7% reduction in their shoulder height relative to crank height, potentially affecting shoulder extension, as previously suggested . Between recreational and competitive groups, participant's classification, handbike configurations, and backrest shapes were comparable, therefore, the observed technical differences may be attributed to the greater skill level the competitive participants . The greater skill of the handcyclists in the competitive group potentially facilitated their greater power output.…”
Section: Discussionmentioning
confidence: 64%
“…Crank angle was then determined using Euler angles (ZXY sequence). Upper limb kinematics were normalized to cycle duration (0%‐100%) and then averaged across ten cycles . These average cycles were then inputted used in the SPM analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Part of the work devoted to the inverse dynamics task assumes the coupling of movement in the ankle with the angle of the crank rotation (Bini, 2016). This is because the ankle joint in comparison to the knee and hip joint has the smallest range of movements in the sagittal plane -the plane of movement of the kinematic elements of the bicycle.…”
Section: Elimination Of Passive Constraints In the Human-bicycle Kinementioning
confidence: 99%